INTEGRASI KEARIFAN LOKAL DALAM MATERI PAI UNTUK PENGUATAN SIKAP TOLERANSI DAN MODERASI BERAGAMA: STUDI ETNOPEDAGOGI DI MTS DAERAH MULTIKULTURAL - Umam, Khotibul; Kurniawan, Sugeng; sabli, Muhammad; Yulia Friska, Sonia; Andryadi; Baili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Islamic Religious Education (PAI) at Islamic junior high schools (MTs) in multicultural regions faces contextual challenges in fostering tolerance and religious moderation amid ethnic, cultural, and religious diversity. This study aims to explore the forms, strategies, and impacts of integrating local wisdom into PAI materials as an ethnopedagogical approach to strengthening tolerance and religious moderation attitudes. The research employed a qualitative design using an ethnopedagogical study approach that combined participatory observation, in-depth interviews, document analysis, and focus group discussions (FGD). Subjects included 4 PAI teachers, 1 cultural/traditional leader, and 24 eighth-grade students at an MTs in a multicultural area, selected purposively. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model and reflexive thematic analysis. Findings identified three relevant forms of local wisdom: (1) the tradition of silih asah-asih-asuh and interfaith mutual cooperation, (2) customary deliberation as a conflict resolution mechanism, and (3) the settlement pattern of adjacent houses of worship symbolizing social cohesion. Pedagogical integration was implemented through contextualization of Module Ajar content, collaborative project-based learning, reflective dialogue, and attitude portfolio assessment. Results indicate that the ethnopedagogical approach effectively strengthens cognitive understanding (diversity as sunnatullah), affective internalization (empathy, prejudice reduction), and behavioral manifestation (cross-background cooperation, inclusive language, conflict mediation) among students. The study concludes that local wisdom serves as a pedagogical wasilah bridging universal Islamic values with socio-cultural contexts, making PAI more relevant, transformative, and contextual. Recommendations include developing standardized ethnopedagogical modules, teacher training through Professional Learning Communities (PLCs), and flexible policy support from the Ministry of Religious Affairs and Ministry of Education.